THE CORRELATION BETWEEN 7TH GRADE JUNIOR HIGH SCHOOL STUDENTS’ LEARNING STYLE AND THEIR FIRST SEMESTER EXAMINATION SCORE - Ummi Nadhiroh (Al-Shobar Publisher, Yayasan Islam Al-Shobar Rawaurip, 2023)
Every person has their own learning style. Visual, auditory, and kinesthetic become the most common learning style. Knowing the characteristics of each learning style facilitates students' receiving and processing of information or teaching materials presented. Understanding each student's characteristics and learning styles will make it easier for the teacher to develop the teaching and learning process utilizing a number of methods and strategies. This study aimed to find out the learning style that students like and their relationship with their test scores. Data were collected from 31 students in the seventh grade at MTs Muhammadiyah Batur. O' Brien's (1985) questionnaire was used to assess student learning styles. Pearson correlation coefficients analysis was used with the IBM SPSS Statistics 26 application to analyze learning styles for academic achievement. According to data analysis, Kinesthetic learning is the most common used in this study. Pearson correlation coefficient analysis revealed a high correlation or marked relationship between the 7th grade junior high school students learning style and their first-semester examination score. Interestingly, the kinesthetic learning style was discovered to be the most prevalent of the three types of learning and to have a strong correlation with students’ examination scores.